Brief Report: Serpin Spi2A as a Novel Modulator of Hematopoietic Progenitor Cell Formation. (18th August 2014) - Li, Lei; Byrne, Susan M.; Rainville, Nicole; Su, Su; Jachimowicz, Edward; Aucher, Anne; Davis, Daniel M.; Ashton-Rickardt, Philip G.; Wojchowski, Don M.
Abstract : Prime regulation over hematopoietic progenitor cell (HPC) production is exerted by hematopoietins (HPs) and their Janus kinase-coupled receptors (HP-Rs). For HP/HP-R studies, one central challenge in determining specific effects involves the delineation of nonredundant signal transduction factors and their lineage restricted actions. Via loss-of-function studies, we define roles for an HP-regulated Serpina3g /Spi2A intracellular serpin during granulomyelocytic, B-cell, and hematopoietic stem cell (HSC) formation. In granulomyelocytic progenitors, granulocyte macrophage colony stimulating factor (GMCSF) strongly induced Serpina3g expression with Stat5 dependency. Spi2A-knockout (KO) led to 20-fold decreased CFU-GM formation, limited GMCSF-dependent granulocyte formation, and compromised neutrophil survival upon tumor necrosis factor alpha (TNF- α ) exposure. In B-cell progenitors, Serpina3g was an interleukin-7 (IL7) target. Spi2A-KO elevated CFU-preB greater than sixfold and altered B-cell formation in competitive bone marrow transplant (BMT), and CpG challenge experiments. In HSCs, Serpina3g /Spi2A expression was also elevated. Spi2A-KO compromised LT-HSC proliferation (as well as lineage neg Sca1 pos Kit pos (LSK) cell lysosomal integrity), and skewed LSK recovery post 5-FU. Spi2A therefore functions to modulate HP-regulated immune cell and HSC formation post-5-FU challenge. Stem Cells   2014;32:2550–2556